Socialization and Demonstration of Making Anti-Mosquito Spray Using Lemongrass (Cymbopogon citratus) and Zodia Leaves (Evodia suaveolens) as Basic Ingredients - Firmansyah, Gunawan; Aprillia Puspitasari Tunggadewi; Annik Megawati; Mera Putri Pratitis; Yulia Pratiwi; Wildayanti , Wildayanti; Luvita Gabriel Zulkarya; Luthfiana Nurulin Nafi’ah; Bagus Riyanto; Sukarno, Sukarno; Menik Lucta Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health problem in Indonesia, with high case and death rates, including in Kudus Regency. The tropical climate of Rejosari Village and the presence of stagnant water around residents' homes increase the risk of dengue-causing mosquitoes breeding. Furthermore, the community still relies on chemical mosquito repellents. This community service activity aims to improve the knowledge and skills of PKK (Family Welfare Movement) women in making herbal mosquito repellent spray from lemongrass (Cymbopogon citratus) and zodia leaves (Evodia suaveolens) as a safer and more environmentally friendly alternative for vector control. The method used is a participatory approach based on community empowerment through interactive education, discussions, demonstrations, and hands-on practice. The activity stages include problem identification, joint planning, implementation of outreach, demonstration of herbal spray making, participant practice, and evaluation and follow-up in the form of handing over zodia plants to participants. The activity results showed an increase in participants' knowledge about the dangers of dengue fever, environmental-based prevention, and the benefits of herbal plants as natural repellents. Participants were also able to practice making herbal mosquito repellent spray independently. The enthusiasm and active participation of participants demonstrated the growing collective awareness of implementing more sustainable mosquito control at the household level. This activity demonstrated that empowering PKK women through a participatory approach is effective in increasing community capacity in environmentally-based dengue prevention and utilizing local natural materials